Psychometric evaluation of the level of service/case management inventory among Australian offenders completing community-based sentences - Gordon, Heidi (Criminal justice and behavior, 2015)
Risk assessment inventories play a significant role in predicting recidivism risk and informing parole and community supervision orders. This article examines the effectiveness of the Level of Service/Case Management Inventory (LS/CMI) in a study of Australian offenders completing community-based sentences. The study aimed to identify the internal reliability and the factor structure of the LS/CMI. The results indicated that the LS/CMI total score achieved excellent internal reliability. There is concern regarding the capacity for the subscales to function independently. A factor analysis determined a two-factor solution at a subscale level, whereas a more diverse factor solution was obtained at an item level. The LS/CMI was determined to be predictive of recidivism, but this was a weak effect. The results indicate that the LS/CMI as it is currently used in this population may not be an appropriate assessment tool, requiring further research before an international risk assessment is adopted in Australian jurisdictions.